Stochastic Dominance and Mutual Fund Performance - Joy, O. Maurice; Porter, R. Burr (Journal of Financial and Quantitative Analysis, 1974)
Previous empirical studies of mutual fund performance relative to market performance were conducted using two- and three-moment analysis. This study has applied first-, second-, and third-degree stochastic dominance principles to investigate the same question. Our results support the earlier Sharpe study and oppose the recent Arditti work. From the investor's standpoint, mutual fund performance was inferior to market performance over the period 1954–1963.